THE APPLICATION OF ARTIFICIAL INTELLIGENCE TOOLS IN HIGHER EDUCATION: OPPORTUNITIES AND CHALLENGES - Āboliņa, Anda; Mežinska, Silvija; Ļubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The impact of Artificial Intelligence (AI) is visible in both the workplace and in education. The progress in AI usage brings about changes and new opportunities for higher education as a whole, across various professional domains. The implications of AI's impact pose a challenge for higher education institutions because students need to be prepared for professional careers, taking into account both the opportunities and offerings created by AI. The study and daily life with AI are widely discussed topics in various sectors, including education. The aim of the research is to provide an overview of the use of AI tools in higher education, particularly in fields like engineering and design, and to analyze the level of user readiness for their application. Research methods include theoretical aspects such as literature review and analysis of internet resources, as well as empirical methods like focus group discussions and analysis of expert interview data. The research is based on 44 students, 4 lecturers in the field of Information and Communication Technology (ICT), and 1 representative from a company working with AI and Machine Learning (ML). The research period is in the autumn of 2023. The research results offer an overview of existing tools and demonstrate awareness of the impact and application possibilities of AI in studies, as well as the current level of user readiness for using AI tools. They also highlight potential research directions for integrating AI capabilities with the study process to assist teachers and students in understanding the latest AI opportunities, promoting preparedness, and considering AI challenges in the future.